2019
DOI: 10.1111/liv.14063
|View full text |Cite
|
Sign up to set email alerts
|

Second‐line chemotherapy in biliary tract cancer: Outcome and prognostic factors

Abstract: Background & Aims The prognosis of biliary tract cancer (BTC) is poor. Standard treatment for advanced BTC is a chemotherapy (CT) with gemcitabine and cisplatin. Phase III evidence for a second‐line (2L) CT is lacking. We aimed to investigate the feasibility of a 2L CT, to estimate the outcome and to identify prognostic markers. Methods Patients of our institution with advanced BTC between 2000 and 2015 receiving CT were included. Data were analysed in univariate and multivariate analysis. Results Three‐hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…When patients show cancer progression after first-line chemotherapy, a good PS ECOG is the most important selection factor for the activation of second-line therapy [30].…”
Section: Chemotherapy For Metastatic Disease: First and Second Linesmentioning
confidence: 99%
“…When patients show cancer progression after first-line chemotherapy, a good PS ECOG is the most important selection factor for the activation of second-line therapy [30].…”
Section: Chemotherapy For Metastatic Disease: First and Second Linesmentioning
confidence: 99%
“…Although the available data suggested that a subpopulation of patients, especially young patients and those with a good PS, could benefit from second-line chemotherapy, this benefit number seemed limited and the evidence was considered to be of insufficient quality (level C) to recommend secondline chemotherapy for aCCA as a standard of care strategy (24). One of the main challenges for the completion of adequately powered studies was the fact that, due to the aggressive behaviour of CCA, few patients (ranging from 10 to 40% in different series) are considered to be eligible for second-line treatment (22,(25)(26)(27)(28). In 2019, results from the ABC-06 clinical trial were reported (29).…”
Section: Second-line Chemotherapymentioning
confidence: 99%
“…Few studies have been conducted in patients with advanced CCA and progression after first-line therapy, so there is no established standard of care for these persons. There are also few data on selecting patients who might benefit from second-line therapy; the available studies consistently required good performance status to initiate second-line therapy [42][43][44][45] . Other prognostic factors are the treatment effect in first-line therapy (disease control or not), a low CA19-9 level, and the absence of peritoneal carcinomatosis [44,45] .…”
Section: Second-line Therapymentioning
confidence: 99%